Effects of myocardial perfusion abnormalities on the accuracy of left ventricular volume and ejection fraction measured by thallium-201 gated single-photon emission tomography: comparison with echocardiography as the reference standard. Issue 11 (November 2015) - Kurisu, Satoshi; Iwasaki, Toshitaka; Abe, Nobukazu; Tamura, Megumi; Ikenaga, Hiroki; Watanabe, Noriaki; Higaki, Tadanao; Shimonaga, Takashi; Ishibashi, Ken; Dohi, Yoshihiro; Fukuda, Yukihiro; Kihara, Yasuki
Abstract : Background: We assessed the accuracy of left ventricular end-diastolic volume (EDV), end-systolic volume (ESV), and ejection fraction (EF) using quantitative gated single-photon emission computed tomography (QGS) in comparison with echocardiography as the reference standard. We also assessed the effects of total perfusion deficit (TPD) on the accuracy of QGS measurements. Methods: A total of 258 patients underwent single-photon emission computed tomography and transthoracic echocardiography within 4 weeks of each investigation for evaluating coronary artery disease. Patients were divided into four groups according to TPD scores. Results: There were 138 patients with no/minimal TPD, 64 patients with small TPD, 35 patients with middle TPD, and 21 patients with large TPD. There were good correlations and agreements in EDV ( r =0.87, 0.90, 0.71, and 0.94, respectively), ESV ( r =0.92, 0.94, 0.79, and 0.94, respectively), and EF ( r =0.61, 0.79, 0.61, and 0.83, respectively) between QGS and echocardiography in patients with any TPD. QGS significantly underestimated EDV and ESV in patients with no/minimal or small TPD, and significantly overestimated ESV in patients with large TPD. QGS significantly underestimated EF in patients with middle or large TPD. Conclusion: Our results suggest that QGS is a useful tool for assessing the left ventricular volume and function in patients with any TPD, but myocardial perfusion abnormalities should be taken into consideration when interpreting QRS measurements.